HARTA DALAM PERSPEKTIF AL-QUR'AN: STUDI TAFSIR MAUDHU'I - Fauzul Iman (Al Qalam, 2011)
Almost every human needs wealth because it becomes a supporting tool for human life in the World. Besides, it also becomes both the help and the load for its owners in the hereafter. Nobody does not need wealth. Indeed, one ungrudgingfy goes early and comes in the dark time to earn the money. Ructions and losing of soul sometimes happened because of fighting over the wealth. Wealth is a tryout (slander) for human (Q.S. at-Tagabun: 15). Because of wealth one may enter into either the heaven or the hell. This article tries to discuss on the wealth based on the Qur'an. Based on the Quranic perspective, wealth is not merely a tool for satisfying for human needs, but it becomes a medium God mates for human in which it may become either comfort or curse for human being. Wealth, according to the Qur'an, has several functions. Firstly, it becomes a tryout (slander) for human, whether one will be grateful or vice versa. Secondly, it may also become mata' al-hayat ad-dunya (wordly fixings). Thirdly, it becomes wasilat al-jihad (means for jihad) for the owners. Key Words: wealth, slander, wordly fixings, means for jihad.